Knowledge and attitudes to vitamin D and sun exposure in elite New Zealand athletes: a cross-sectional study - Walker, N.; Love, T. D.; Baker, D.; Healey, P.; Haszard, J.; Edwards, S.; Black, K. (Journal of the International Society of Sports Nutrition, 2014)
Background: Sun safety and vitamin D status are important for prolonged health. They are of particular interest to those working with athletes for whom for whom safe sun practices maybe limited.The aim of this cross-sectional study was to describe the attitudes of elite New Zealand athletes to both vitamin D and sun exposure. Methods: 110 elite New Zealand outdoor athletes volunteered to participate in an interview with a trained interviewer. The interviewer asked the athletes questions on their Vitamin D knowledge, attitudes and practices regarding sun exposure as well as their concerns about skin cancer. Results: Athletes were more concerned about their risk of skin cancer (66%) than their vitamin D status (6%). Although the majority (97%) were aware of Vitamin D and could identify the sun as a source (76%) only 17% could name another source of Vitamin D.Only 10 (9%) reported always applying sunscreen before going out in the sun. No athlete reported reapplying sunscreen every hour and 25 suggesting that they never reapply sunscreen. Conclusions: Athletes are concerned about skin cancer however, their use of sunscreen is not optimal suggesting reapplication of sunscreen could be targeted in order to reduce the risk of sun cancer. Awareness of sources of Vitamin D other than the sun may also need to be improved potentially through educational interventions and possibly in conjunction with sun smart messages.